(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2019)
In this paper, a single element antenna is designed at millimeter-wave frequency bands for future 5G smartphone applications. The configuration of proposed antenna is multiple L-slots on the ground plane which is designed on a low cost FR4 board. The antenna covers a frequency range between 28 to 35 GHz with a higher bandwidth 4.7 GHz. The antenna shows an excellent performance when integrated with the mobile phone application. The single element antenna exhibits a maximum radiation pattern around 5.945 dBi.